The Roads of the Others: E. Levinas and T. Adorno - Mažeikis, Gintautas (Problemos, 2022)
In this article, Levinas’ philosophy is interpreted as an ethical and Talmudic consideration of existential paths. After Auschwitz, the concept of otherness and the diversity of other faces presupposes a free and diverse “being on the road,” an ethics of journey, and denies theodicy and an essentialist interpretation of being. The thesis is proven by comparing Levinas’, Baranova’s and Adorno’s approaches to ethics and Exegesis. Levinas’ philosophy is elaborated by referring to the exegetics of the Exodus and the concept of an incomprehensibility of Auschwitz. The author discusses the philosophies of Levinas and Adorno who both consider the Holocaust as an occurrence not open to interpretation. Levinas advocates the end of theodicy as a justification for divine history and argues the primacy of ethics, while Adorno develops anti-theodicy and presents the relevance of critique of instrumental reason.